2007
DOI: 10.1002/adfm.200600751
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Supramolecular Nanovalves Reconfigured for Light Activation

Abstract: All autonomous machines share the same requirement—namely, they need some form of energy to perform their operations and nanovalves are no exception. Supramolecular nanovalves constructed from [2]pseudorotaxanes—behaving as dissociatable complexes attached to mesoporous silica which acts as a supporting platform and reservoir—rely on donor‐acceptor and hydrogen bonding interactions between the ring component and the linear component to control the ON and OFF states. The method of operation of these supramolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
142
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(144 citation statements)
references
References 63 publications
0
142
0
1
Order By: Relevance
“…56,57 Zink and Stoddart prepared several gated materials triggered by redox inputs that were equipped with nanovalves based on rotaxanes and pseudorotaxanes containing redox active moieties. [58][59][60][61][62] Apart from the examples described above, which use redox-, light-and pH-triggered systems, some additional exploratory studies that use alternative external stimuli such as temperature 63 and the presence of certain anions 64 have also been reported. Another use of these hybrid gated nanomaterials deals with the development of new signaling protocols.…”
mentioning
confidence: 99%
“…56,57 Zink and Stoddart prepared several gated materials triggered by redox inputs that were equipped with nanovalves based on rotaxanes and pseudorotaxanes containing redox active moieties. [58][59][60][61][62] Apart from the examples described above, which use redox-, light-and pH-triggered systems, some additional exploratory studies that use alternative external stimuli such as temperature 63 and the presence of certain anions 64 have also been reported. Another use of these hybrid gated nanomaterials deals with the development of new signaling protocols.…”
mentioning
confidence: 99%
“…Many studies have reported the design of responsive caps, such as nanoparticles, polymers, supramolecular assembles and biomolecules, to control drug release from MSN in response to different stimuli including pH, temperature, light, redox activation, enzymes, competitive binding, etc. [5][6][7][8][9][10][11][12][13] Of the stimuli previously reported, the construction of pH-triggered caps was one of the most efficient strategies for controlled drug release due to the different pH environment in cells, tissue or body. [14][15][16][17] For example, the interstitial or extracellular environment in tumors tends to be more acidic than the normal tissues, and the endosomes/lysosomes in cancer cells exhibit even lower pH values.…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of drug delivery, a sophisticated nanodelivery system, which is capable of storing and protecting drug molecules, controlling and regulating release of cargo molecules only at target site, is unequivocally desired. In this regard, release of the drugs or active agents from nanocontainers had been successfully demonstrated to be regulated in response to changes in redox potential, 17 pH, 18,19 temperature, 20 light, 21 and the presence of enzymes found in certain diseases. 22 The rate of release of the cargo molecules relies on the shape and geometrical properties of nanocontainers.…”
Section: Introductionmentioning
confidence: 99%